World biofuels production potential - Rommer, Thomas E. (Energy policies, politics and prices series., 2010)
This study by the U.S. Department of Energy (DOE) estimates the worldwide potential to produce biofuels including biofuels for export. It was undertaken to improve our understanding of the potential for imported biofuels to satisfy the requirements of Title II of the 2007 Energy Independence and Security Act (EISA) in the coming decades.